2007
DOI: 10.2522/ptj.20050244
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Neuromuscular Electrical Stimulation on Ankle Swelling in the Early Period After Ankle Sprain

Abstract: The results indicate that NMES, as designed and used in this study, is not effective in decreasing ankle-foot volume or increasing self-assessed ankle function in the early period after ankle sprain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(51 citation statements)
references
References 24 publications
1
49
1
Order By: Relevance
“…We did not exclude based upon grade of ankle sprain or whether the ankle sprains were first time or recurrent ankle sprains. Of the sixteen studies assessed for eligibility, only four studies (Man et al, 2007;Mendel et al, 2010;Michlovitz et al, 1988;Sandoval et al, 2010) satisfied the inclusion criteria and were included for analysis.…”
Section: Criteria For Selecting Studiesmentioning
confidence: 99%
“…We did not exclude based upon grade of ankle sprain or whether the ankle sprains were first time or recurrent ankle sprains. Of the sixteen studies assessed for eligibility, only four studies (Man et al, 2007;Mendel et al, 2010;Michlovitz et al, 1988;Sandoval et al, 2010) satisfied the inclusion criteria and were included for analysis.…”
Section: Criteria For Selecting Studiesmentioning
confidence: 99%
“…Taylor et al 28 found that only HVPC(-), but not the alternating current, caused reductions in the output of macromolecules from microvessels of capillaries of hamsters with post-traumatic edema. Man, Morrissey, and Cywinski 16 , in a recent study, used low voltage currents to treat ankle edema in humans, but also reported no significant differences compared to the CG.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in edema using this intensity has been shown in several animal studies 7,8,[10][11]25,27,28 . Another study used a current at motor threshold in the treatment of ankle sprain (acute phase) in humans and found no difference between the treatment group and the CG 16 . It is difficult to compare the results of these studies because, in addition to using different levels of stimulation, they were also performed with different species (animals and humans).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Man et al 164 found no significant difference in ankle and foot volume, girth, and self-perceived functioning in individuals with acute ankle sprains receiving electrical stimulation at either motor or submotor intensity.…”
Section: Electrotherapymentioning
confidence: 99%